KEPEMIMPINAN SEKOLAH DALAM KRISIS KESEHATAN MENTAL PESERTA DIDIK: RESPON DARURAT DAN PRAKTIK TERBAIK - M. Taufiqurohman (CV. Adiba Aisha Amira, 2025)
The mental health crisis among students has become a serious challenge for educational institutions, particularly in the post-pandemic era which has introduced new psychosocial pressures. This study aims to explore the role of school leadership in responding to the mental health crisis among students at Madrasah Aliyah Al Amiriyyah and to identify best practices implemented. A qualitative case study approach was employed, with data collected through in-depth interviews, observations, and documentation. The findings reveal that the madrasah leadership adopted an emergency response approach through cross-functional collaboration involving guidance counselors, homeroom teachers, and parents. The principal played a key role in fostering a school culture that is empathetic and supportive of students’ mental health. This aligns with Michael Fullan’s (2007) view that effective educational leaders are those who can guide change within complex systems with a focus on learning and well-being. Additionally, Suyatno (2016) emphasized that transformative leadership in the context of Islamic education is marked by moral and spiritual commitment to nurturing students' character and well-being. Best practices implemented include teacher training in early detection of psychological disorders, the integration of spiritual values into counseling, and the formation of an internal school crisis response team. This study underscores the importance of collaborative and spiritually grounded leadership in addressing mental health crises within religious educational institutions.